Phytotoxicity of mineral, vegetable oils and foliar fertilizers in coffee seedlings - Santos, Leandro Alvarenga; Pozza, Edson Ampélio; Souza, Paulo Estevão de (Coffee Science - ISSN 1984-3909, 2017)
The objective of this study was to evaluate the toxicity in coffee seedlings caused by mineral oil, vegetable and foliar fertilizer, applied in different radiation intensities. In the first experiment not observed symptoms of phytotoxicity in the control plants and sprayed with foliar fertilizer. Two experiments to study the phytotoxic action of oils and foliar fertilizers were performed. The first was evaluated phytotoxic effects of mineral oil, vegetable oil and foliar fertilizer in different application times. In the second experiment evaluated the intensity of radiation in the occurrence of toxicity symptoms caused by both oils. At the end of the second experiment samples were taken to perform scanning electron microscopy. Plants sprayed 12:00 h had higher incidence and severity of injuries to both oils in relation to others (9:00 and 17:00h). In the light intensity experiment proved that the increase of light intensity from 80 to 320 µMol/m²/s promoted an increase in symptoms of phytotoxicity. In the analysis of lesions by scanning electron microscopy, deformations on the leaf surface caused by mineral oil and also for vegetable oil were observed.